'Eligibility regulations for the female classification': somatechnics, women's bodies, and elite sport. Issue 2 (3rd April 2022) - Brömdal, Annette; Rasmussen, Mary Lou
ABSTRACT: Employing Nikki Sullivan's notion of somatechnics, this article looks at the bodies of women athletes as sites of embodied subjectivity and considers how they are marked in medical discourses produced by significant cultural entities such as sporting governing bodies and their medical experts involved in the management and treatment of women athletes born with particular intersex variations. Somatechnics is understood in this paper as co-constitutive by developing understanding of how bodies are seen and produced in ways that are always already intertwined. To do this, we draw on two interviews with Dr Patrick Schamasch, the former Medical and Scientific Director of the International Olympic Committee and Dr Hermina Schneider, a Sports Medicine Expert of a European National Olympic Committee and their unique, unreported, and unofficial discourses and actions concerning contemporary eligibility regulations/tests in women's sport. Building on the notion of somatechnics, our, focus is on developing understanding of the regulation of the corporeality of women athletes. Our aim is not to elucidate the truth of such regulations, but to contribute to an understanding of how modificatory practices aimed at women athletes endure, and the rationales governing the thinking behind those who are the authors of eligibility regulations for the female classification.